Analisis Framing Pemberitaan Relokasi Pulau Rempang pada Media Online kompas.com dan detik.com - Wibowo, Anita Yasmin; Triyono, Agus (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research was carried out using Robert Entman's framing model analysis on the online media kompas.com and detik.com. This research discusses the relocation of Rempang Island in the period September-November 2023. This research uses a qualitative approach. The object of this research is the Relocation of Rempang Island, which is a Government project, namely the development of the area that will become Rempang Eco City. The relocation of Rempang Island which is on Batam Island, Riau Islands, is a government project which has long been planned to build Rempang Eco City but only in 2023 will this development get investors so that this development can be realized, as a result of this the government has to carry out the relocation to the residents of Rempang, as a result of this there were demonstrations and clashes demanding that they not be relocated, demanding rights and clarity regarding this relocation issue from the government. The results of the research focus more on the meaning and prominence of messages in several news frames on kompas.com and detik.com.